2022
DOI: 10.1128/mbio.02213-22
|View full text |Cite
|
Sign up to set email alerts
|

The Urethral Microbiota of Men with and without Idiopathic Urethritis

Abstract: Nongonococcal urethritis (NGU) is the commonest genital tract syndrome in men and is nearly universally presumptively treated with an antibiotic. Common causes of NGU include Chlamydia trachomatis and Mycoplasma genitalium , but in more than 50% of cases, an infectious cause is not identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…Our study is the first of which we are aware to analyze the tissue-level microbiome of the foreskin. Consistent with previous reports using penile swabs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)48), the bacteria we identified are predominated by taxa commonly colonizing the skin (chiefly Corynebacteria spp) (49,50) in addition to anaerobic bacteria such as Prevotella, Dialister, Murdochiella, Peptoniphilus, and Negativicoccus. These anaerobic species have been associated with increased inflammation and HIV acquisition in uncircumcised men (8) and bacterial vaginosis in women (51).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study is the first of which we are aware to analyze the tissue-level microbiome of the foreskin. Consistent with previous reports using penile swabs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)48), the bacteria we identified are predominated by taxa commonly colonizing the skin (chiefly Corynebacteria spp) (49,50) in addition to anaerobic bacteria such as Prevotella, Dialister, Murdochiella, Peptoniphilus, and Negativicoccus. These anaerobic species have been associated with increased inflammation and HIV acquisition in uncircumcised men (8) and bacterial vaginosis in women (51).…”
Section: Discussionsupporting
confidence: 90%
“…While condom use (1,2), pre-exposure prophylaxis (PrEP) (3), and medical penile circumcision (4) are effective at reducing HIV incidence in men, the contribution of the penile microbiome to these mechanisms has not been fully explored. Previous work has shown a predominance of anaerobic species in the microbiota of swabs taken from the coronal sulcus or urethra (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and have reported associations between species such as Prevotella and increased mucosal inflammation, HIV target cell density and risk of HIV acquisition (8,16).…”
Section: Introductionmentioning
confidence: 99%
“…The urethra is the common duct for the evacuation of urine and the transition of semen throughout the penis. Several studies have analysed the bacterial content of the urethra by analysing first void urine samples [ 41 , 42 , 43 ]. Nevertheless, it is still not clear whether the observed taxa were present specifically in the urethra or are part of the bladder microbiota, which has not been fully elucidated yet [ 44 ].…”
Section: Microbiota Of the Mgtmentioning
confidence: 99%
“…Bacterial colonisation of the urethra has also been studied in the context of idiopathic urethritis [ 43 ]. The results suggested that microbiota is significantly different between controls and men with urethritis and that the sex of the partner also influenced the composition of the microbiota.…”
Section: Microbiota Of the Mgtmentioning
confidence: 99%
“…Among adolescent men, certain bacterial genera were only detected in urine from sexually active men, suggesting colonization via urethral sexual exposures. 7 Some cross-sectional studies have detected associations between vaginal sex and specific bacteria/taxa or community type 8,9 ; others have not detected associations with sexual exposures. [10][11][12] One cross-sectional study suggested that vaginal sex impacts the urethral microbiota but identified little to no evidence of an association between insertive oral sex (IOS) or insertive anal intercourse (IAI) and the urethral microbiota.…”
mentioning
confidence: 99%